Chaser : unlocking the genius of the dog who knows a thousand words - Pilley, John W. frey50; Hinzmann, Hilary (Detroit Gale Cengage Learning, 2013)
Chaser has a way with words. She knows over a thousand of them -- more than any other animal of any species except humans. And she and her owner/trainer, retired psychologist John Pilley, have now demonstrated her ability to understand sentences with multiple elements of grammar and to learn new behaviors by imitation. John's work with Chaser offers a fresh perspective on what's possible in the relationship between a dog and a human.
The Dog Who Knows a Thousand Words -- Good-bye -- Christmas in June -- Let the Puppy Be a Puppy -- "You've Got To Name Her Chaser!" -- Chaser Learns What Not To Chase -- Listening to the Farmer -- Learning by Playing -- Herding Words -- Herding Sheep -- Advanced Lessons -- Getting Published -- Going Viral -- Chaser Takes a Bow -- Chaser Goes to Washington -- Expanding the Conversation.
Keywords: Chaser; Dogs -- Psychology; Dogs -- Training; Human-animal communication; Large type books